Quality from the Production Cooperatives Perspective (Publicaciones en Ciencias y Tecnología, 2024)
The social economy aims to minimize the various economic and social imbalances. For this reason, the role of production cooperatives as social economy organizations seeking the right balance between their economic and social objectives is particularly important. However, some studies point out the difficulties that production cooperatives have had to face in order to remain in the market and fulfill their purpose. Some weaknesses include administrative aspects, lack of knowledge of expected results in terms of quality, costs, quantities to be produced, and difficulty in maintaining their dual economic and social role. In addition to the above, the works found on quality in production cooperatives are limited to the application of models designed for companies with an economic purpose. In view of this reality, we have considered constructing, through documentary research on aspects of social economy and quality, a definition of quality in production cooperatives as a starting point to improve the functioning of these organizations. In this regard, this article aims to propose a definition of quality in production cooperatives that takes into consideration their nature as organizations with an economic development objective but from a perspective that puts human and social development first
Keywords: Quality; production; conceptual review; stakeholders; social economy